Strategi Pemasaran Berbasis Digital Marketing Terhadap Kualitas Layanan (Studi Kasus Pada Bkkbisa) - Atika Dwi Mabruroh; Puji Isyanto; Dini Yani (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
A marketing strategy based on Digital Marketing is an effective marketing strategy because it can provide a very large role for the progress of the development of a company. With the trend of using the internet in Indonesia which is already very large, companies are increasingly taking advantage of digital developments which are increasing over time by implementing their marketing strategy as one of their tactics to increase company traffic and achieve the expected targets. This study aims to determine how much influence the implementation of digitalbased marketing strategies has on service quality at BKKBISA. This research method is a qualitative approach using a case study model and a phenomenological method. Respondents in this study were BKKBISA users throughout the island of Java, Indonesia. The study population was 382,199 people and a sample of 100 respondents using BKKBISA. The data collection technique was carried out through structured interviews on a Likert scale and distributed via Google form. The results of this study indicate that digital marketing plays a major role in BKKBISA's marketing strategy which is carried out digitally so that it affects the quality of services available at BKKBISA.